Compact Conjugated Polymer Dots with Covalently Incorporated Metalloporphyrins for Hypoxia Bioimaging. (30th November 2018) - Fang, Xiaofeng; Ju, Bo; Liu, Zhihe; Wang, Fei; Xi, Guan; Sun, Zezhou; Chen, Haobin; Sui, Changxiang; Wang, Mingxue; Wu, Changfeng
Abstract: Hypoxia is closely related to multiple diseases, especially in tumors, which increases the aggressiveness and drug resistance of cancer cells. Precise hypoxia imaging is of great significance for cancer diagnosis and the evaluation of therapeutic effects. A kind of hydrophobic polymer (i.e., PFPtTFPP) as an imaging probe for hypoxia with fluorene as an energy donor and an oxygen‐sensitive Pt II porphyrin as an energy acceptor was developed. Compact polymer dots (Pdots) with a small size were prepared by nanoprecipitation. The PFPtTFPP Pdots showed excellent hypoxia sensing in solution with high sensitivity and full reversibility. The emission intensity, quantum yields, lifetime, and single‐particle brightness significantly increased under hypoxia conditions. Remarkably, hypoxia imaging in vitro and in vivo was realized, and a clear increase in brightness was observed under hypoxia conditions and in the tumor area. Excellent hypoxia imaging ability is beneficial to potential applications in cancer diagnosis. Abstract : Connect the dots : Hypoxia is closely associated with many diseases, especially tumors. Precise hypoxia imaging is of great significance for cancer diagnosis and evaluating therapeutic effects. Compact polymer dots comprising a fluorene moiety and an oxygen‐sensitive Pt II porphyrin were developed as an imaging probe for hypoxia allowing imaging in vitro and in vivo with excellent sensitivity and full reversibility.